PENGATURAN PENGELOLAAN DAN REKLAMASI WILAYAH PESISIR DAN PULAU-PULAU KECIL - Dedeng, Dedeng; Asuan, Asuan; Saputra, Ricky (Faculty of Law, University of Palembang, 2024)
Abstract Small Island and coastal areas contain abundant natural resources, both biological and non-biological resources. Apart from that, there is the potential for tourism as another source of income for the country. Indonesia as an archipelago and maritime country has around 17,504 islands and a sea area of 5.8 milion km2, consisting of a territorial sea area of 0.3 milion km2, an archipelagic water area of 2, 95 million km2, and an areaof Indonesia’s EEZ of 2,55 million km2. Apart from small island, there are also coastal areas in various provinces,regencies/cities. The value of natural resources can be an importantsource of income for countries and regions where coastal areas are found. Therefore, it is necessary to regulate management and reclamation from the aspect of regislation regarding small islands and coastal areas. So that throught legal regulations we can orderly maximize income and management and reclamation for the state of small islands and coastel areas. This reaserch uses normative method trought a conceptual approach and a statutory approach. The resultsof this research show that small island and coastal areas have been regulated through statutory regulations, namely in the aspects of management and reclamation and there have been several changes to the law governing small islands and coastal areas. Finally, management is regulated in Laws and Ministerial Regulations, namely Law Number 1 of 2014 concerning Amendments to Law Number 27 of 2007 concerning Coastal Areas. Furthermore, Law Number 1 of 2014 was amended by Perpu Number 2 of 2022 concerning Job Creation and Regulation regarding technical planning for management of coastal areas and small islands regulated through Minister of Maritime Affairs Regulation No. 23 /PERMEN-KP/2016 as well as for Reclamation of coastal and island areas -Small islands are regulated in Presidential Decree Number 122 of 2012 (Presidential Decree No. 122/2012). The suggestion is that this arrangement should also be followed through the formation of Regional Regulations where coastal areas and small islands are located in the Province, Regency/City area so that regions can also utilize these resources in their respective regions. Keywords: Coastal Area; Small Islands; and Legislative Regulations.